Patient Centricity and Pharmaceutical Companies: Is It Feasible?. (July 2017) - du Plessis, Danie; Sake, John-Kenneth; Halling, Katarina; Morgan, Jackie; Georgieva, Anna; Bertelsen, Neil
Various health care bodies (regulatory, health technology assessment, academia, health care providers, scientific journals) request patient input in their decision-making processes. This represents a shift from disease-centered to patient-centered approaches to health care. What does this "patient centricity" mean for the pharmaceutical industry? A panel of senior pharmaceutical industry representatives discussed the following key issues: why the pharmaceutical industry needs to be part of the patient-centric movement; how the industry can become patient-centric; and what a patient-centric company actually does. We summarize the panel's point of view on these key questions. The industry's role has been to develop the science and medicines for prevention or treatment of disease. In response to changes in the current health care environment, the industry should focus its efforts on initiatives that will improve impact and value for patients and carers. True patient centricity requires a change in the industry's cultural mindset, an increase in public trust, clearer roles and responsibilities within pharmaceutical organizations, openness to learn from others, and a framework to measure success. There are examples of industry engagement with patients throughout the drug discovery and development process. Patient-reported outcomes are becoming increasingly important endpoints in trials; they capture information of relevance to patients, identify preferences, and better inform treatment decision making. Understanding the patient experience can improve disease management at critical points in the disease course. The future of patient centricity lies in coordinated efforts by and alignment of multiple health care stakeholders, which can only be achieved through collaborations and consortia, with the industry playing a key role.